Balancing Risk and Caution: The Precautionary Principle in Indonesian Environmental Law Context - Proyogo, Joshua Wijaya (Faculty of Law, Universitas Negeri Semarang, 2024)
This paper explores the application of the precautionary principle within the framework of Indonesian environmental law, emphasizing the delicate balance between risk assessment and precautionary measures. It examines the evolution of the precautionary principle in Indonesian legal discourse and its integration into environmental policy-making and decision-making processes. The analysis sheds light on the challenges and opportunities inherent in applying the precautionary principle within Indonesia's diverse environmental contexts. It highlights instances where precautionary measures have been effectively employed to mitigate environmental risks, while also addressing concerns regarding the potential for regulatory overreach and hindrances to economic development. By delving into case studies and legislative frameworks, this paper provides insights into how the precautionary principle is interpreted and operationalized within Indonesian environmental law. It underscores the importance of incorporating scientific uncertainty and environmental ethics into policy formulation, while also emphasizing the need for flexibility and adaptability in responding to emerging environmental threats. Furthermore, the paper discusses avenues for enhancing the implementation of the precautionary principle in Indonesia, including capacity-building initiatives, stakeholder engagement, and the promotion of interdisciplinary research and collaboration. In conclusion, the paper highlights the significance of striking a balance between risk assessment and precautionary action in Indonesian environmental law. It underscores the importance of a nuanced approach that considers scientific evidence, societal values, and the principles of sustainable development in addressing environmental challenges while fostering economic growth and social welfare.Precautionary Principle